The Cuban Democracy Act of 1992: The International Implications - Cameron, Joanna R. (Tufts Archival Research Center, 2005)
Volume 20, Issue 1. Winter/Spring Now that the original cause for the Cuban embargo has ended, the United States must acknowledge the costs of the embargo and repeal the Cuban Democracy Act.